2017
DOI: 10.1002/hep.29137
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of patients waitlisted for liver transplant with all‐oral direct‐acting antivirals is a cost‐effective treatment strategy in the United States

Abstract: The timing of initiation of antiviral treatment for HCV patients with HCC or DCC relative to LT is an important area of clinical and policy research; our results indicate that pre-LT treatment with a highly effective, all-oral DAA regimen provides the best health outcomes and is the most cost-effective strategy for the treatment of HCV patients with HCC or DCC waitlisted for LT. (Hepatology 2017;66:46-56).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 40 publications
(66 reference statements)
0
24
1
Order By: Relevance
“…24,29 Pretransplant patients who are pre-cirrhotic or who have well-compensated disease may benefit from early HCV treatment with stabilization or regression of chronic liver disease, potentially avoiding LT entirely. Ahmed et al recently reported a Markov analysis comparing delayed or immediate HCV treatment among patient waiting for LT. 30 The benefit of HCV treatment varied according to clinical condition. Among patients with decompensated liver disease, pre-LT treatment was associated with improved survival (9.3 vs. 8.7 quality-adjusted life-years) but higher costs ($304,800 USD vs. $283,789 USD).…”
Section: Discussionmentioning
confidence: 99%
“…24,29 Pretransplant patients who are pre-cirrhotic or who have well-compensated disease may benefit from early HCV treatment with stabilization or regression of chronic liver disease, potentially avoiding LT entirely. Ahmed et al recently reported a Markov analysis comparing delayed or immediate HCV treatment among patient waiting for LT. 30 The benefit of HCV treatment varied according to clinical condition. Among patients with decompensated liver disease, pre-LT treatment was associated with improved survival (9.3 vs. 8.7 quality-adjusted life-years) but higher costs ($304,800 USD vs. $283,789 USD).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have investigated the optimal timing of DAA treatment for patients listed for transplant, using a decision analytical model . The first was the study by Njei et al that considered only patients with decompensated cirrhosis without HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Once again, the PRE‐LT treatment emerged as more effective for patients with a MELD score lower than 23. A final study from Ahmed et al considered patients with decompensated cirrhosis or with HCC in the same model and showed that antiviral therapy given PRE‐LT was more cost‐effective than if given post‐LT. In all these studies, the positive effect of treating with DAA prior to LT was ascribed to a reduction in the MELD score and to a consequent lower risk of death while waiting for a LT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…
We read with interest the study by Ahmed et al (1) identifying the cost-effectiveness of all direct-acting antivirals (DAAs) for patients with hepatitis C virus (HCV) awaiting liver transplant (LT) in the United States.A few things should be considered before applying the findings of Ahmed et al (1) to clinical practice. There are possible selection biases in the base case scenario, for example, the ASTRAL-4 cohort, (2) which may not reflect the full spectrum of the US population.
…”
mentioning
confidence: 99%